2013
DOI: 10.1371/journal.pone.0076399
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Confirmation of O-GlcNAcylated Proteins in Rat Liver Mitochondria by Combination of Mass Spectrometry and Immunological Methods

Abstract: O-linked β-N-acetylglucosamine (O-GlcNAc) is an important post-translational modification (PTM) consisting of a single N-acetylglucosamine moiety attached via an O-β-glycosidic linkage to serine and threonine residues. Glycosylation with O-GlcNAc occurs on myriad nuclear and cytosolic proteins from almost all functional classes. However, with respect to O-GlcNAcylated proteins special in mitochondria, little attention has been paid. In this study, we combined mass spectrometry and immunological methods to perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 56 publications
(61 reference statements)
0
38
0
Order By: Relevance
“…brain synaptosomes and liver) using different approaches (11,33,34). Moreover, three O-GlcNAc sites on these proteins have also been unambiguously detected (supplemental Table 2) 11, 33, 34).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…brain synaptosomes and liver) using different approaches (11,33,34). Moreover, three O-GlcNAc sites on these proteins have also been unambiguously detected (supplemental Table 2) 11, 33, 34).…”
Section: Resultsmentioning
confidence: 86%
“…Very recently, several mitochondrial proteins have been identified from different tissues of rodents (i.e. heart (11), liver (34), and brain synaptosomes (33)) by advanced mass spectrometry techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, O-GlcNAcylation might protect against oxidative stress and promote mitochondrial respiration in the aged retina. In a recent and interesting report, Cao et al (2013) confirmed the significance of O-GlcNAcylation in mitochondrial functionality. The authors demonstrated that mitochondrial proteins in the rat liver are O-GlcNAcylated, and that most of these enzymes are involved in the urea cycle, tricarboxylic acid cycle, and lipid metabolism.…”
Section: Perspectivementioning
confidence: 76%
“…Analysis of the subset of proteins for which mammalian orthologs could be reliably established (79/160) revealed that 24% of these have also been reported to be O-GlcNAcylated in rodents or humans (Table S1) (24)(25)(26)(27). This analysis is likely biased by the limited depth of the O-glycoproteome data available currently, and we expect the overlap to increase with deeper characterization of the two glycoproteomes.…”
Section: Resultsmentioning
confidence: 99%